Efektivitas Inokulum Tunggal dan Konsorsium Fungi Mikoriza Arbuskula pada Pembibitan Tanaman Indigofera zollingeriana: Effectiveness of Single and Consortium Arbuscular Mycorrhizal Fungi Inoculum on Indigofera zollingeriana Plant Nurseries - Muhammad Rizky Pratama; Iwan Prihantoro; Panca Dewi Karti (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2023)
Arbuscular mycorrhizal fungi (AMF) are potential biofertilizers for plants. The succeed and quality of AMF inoculation is related to the type of AMF and plants. This study aimed to find the most effective AMF species in Indigofera zollingeriana nurseries. This experiment study was designed using a completely randomized design with six treatments and five replications based on different types of AMF in single and consortium forms. Treatment details include: IFMIX (consortium: a mixture of five types of AMF), IFTE (Glomus etinucatum), IFTM (Glomus manihotis), IFTA (Acaulospora tuberculata), IFTG (Gigaspora margarita), IFTS Glomus sp. Data were analyzed using Analysis of Variance (ANOVA) and Duncan's Multiple Range Test. Based on the results of variance, AMF inoculation at Indigofera zollingeriana nurseries in a single form (IFTE, IFTM, IFTA, IFTG, and IFTS) resulted in effectiveness that was not significantly different with the consortium FMA inoculation (IFMIX) against AMF colonization, plant height, stem diameter, fresh and dry biomass of plants. Inoculation of inoculums in a single IFTE form resulted in a higher colonization value (p<0.05) than single inoculums IFTA and IFTM. It can be concluded that inoculation of a single AMF (Glomus etinucatum, Glomus manihotis, Acaulospora tuberculata, Gigaspora margarita, Glomus sp.) against AMF consortium produced the same symbiotic effectiveness on root colonization, morphological response and plant biomass production level in Indigofera zollingeriana nurseries. The root colonization rate of a single IFTE inoculum was better than a single inoculum of IFTA and IFTM. Key words: consortium AMF, Indigofera zollingeriana nurseries, single AMF